Enhancing Climate Resilience through Tailored Agro-Climate Advisory Services in Ethiopia - Rettie, Fasil M; Asgaw, Temesgen G (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
In response to increasing food demand and climate variability, digital agricultural solutions have emerged as critical tools for boosting productivity and mitigating environmental risks. The International Maize and Wheat Improvement Center (CIMMYT), in partnership with Green Agro Solution PLC (GAS), is leading a public-private initiative to deliver timely, localized climate advisories to smallholder farmers and extension agents. This initiative leverages platforms such as the Ethiopian Digital Agro-Climate Advisory Platform (EDACaP) and the LERSHA mobile application to disseminate seasonal and sub-seasonal forecasts, agronomic recommendations, and alerts regarding wheat rust. To date, over 373,606 farmers have been reached through 6,566 extension agents, improving access to inputs, mechanization services, and financial tools. This report outlines the methodologies used to develop these advisories and presents key results from the 2024 and 2025 growing seasons, highlighting their role in promoting climate-smart agriculture.